2020
DOI: 10.1016/j.childyouth.2020.104869
|View full text |Cite
|
Sign up to set email alerts
|

Child poverty, status of rural women and education in sub Saharan Africa

Abstract: 4Africa's disadvantaged children are rural, malnourished, out of school, child brides or child labourers 5 and have illiterate mothers who were denied access to productive resources. Our objective is to analyse 6 factors affecting child poverty. Endogenous variables are under five mortality rate, primary school 7 enrolment and child underweight. Endogeneity led to the use of Three Stages Least Squares simultaneous 8 equations and fixed effects methods. The estimated elasticities indicate that female employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…According to the Central Statistics Agency (2019), development programs that have been implemented so far have always paid great attention to poverty alleviation effo rts because the development carried out aims to improve the community's welfare. Poverty is a condition in which people cannot fulfill their basic needs (Ingutia et al, 2020;Kussudyarsana, 2019). Eastern Indonesia has the potential for economic strength in the form of the availability of abundant natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Central Statistics Agency (2019), development programs that have been implemented so far have always paid great attention to poverty alleviation effo rts because the development carried out aims to improve the community's welfare. Poverty is a condition in which people cannot fulfill their basic needs (Ingutia et al, 2020;Kussudyarsana, 2019). Eastern Indonesia has the potential for economic strength in the form of the availability of abundant natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a report by UNICEF (2020), which compiled findings from surveys on national education responses to COVID-19 from 150 countries, showed that schoolchildren in low-income countries were the least likely to access remote learning and the most likely to attend schools with insufficient resources to safeguard operations. Several studies have however suggested that the provision of social services, in terms of education, health care, water and sanitation, enhances productivity and overall quality of life (Schultz and Appleby, 2019;Chireshe and Ocran, 2020;Ingutia et al, 2020). As such, the literature demonstrates the complementarities ICT and the provision of social services among various social services (education, health, water, sanitation and nutrition, for example), as well as between social service provisions and other macroeconomic policy goals (Evans, 2020;Murshed, Bergougui, Badiuzzaman and Pulok, 2020;Park, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both definitions are based on the financial elements that do not represent the whole issue and not describe the reality of poverty in children. This is a different case with the definition according to Ingutia et al (2020), where the children poverty is understood as those whom their rights are denied in getting access to proper supports in term of material, sociocultural, economy, politic, social and environments which are the basic things needed for the children development. This definition describes the issue more adequately because it considers the surrounding elements of the children in poverty.…”
Section: Introductionmentioning
confidence: 99%
“…When their family income is affected, it will also negatively influence the children's development, welfare, education, and nutrition (Ge & Wang, 2019) which then contribute to a long-term effect. According to Ingutia, Rezitis, and Sumelius (2020), with insufficient resources and unacceptable conditions, in terms of nutrition and facilities in the community or family, the children will have difficulties in exploring their potentials. Besides, they also have a high probability of dropping school and paying less attention to learning and education (Ingutia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation